Analysis of Potential and Effectiveness of Groundwater Tax as a Contribution to Locally-Generated Revenue of Malang City in Pandemic Era - Fadilla Cahyaningtyas; Engeline Talitha Rachael Koraag (CV. Inara, 2022)
Groundwater tax is a sub-section of local taxes that support the local revenue of a city or district. The collection must prioritize efficiency and effectiveness in order to meet the targets that have been set. The purpose of this study is to understand and analyze the potential and effectiveness of groundwater tax collection in Malang from 2015 until 2020.The research method that used is using the interview method and descriptive analysis with reference to the theory of absolute tax liability and the principle of domicile. Based on the results of research at the Malang City Regional Revenue Service, the potential for groundwater tax revenue according to the number of registered taxpayers continues to increase every year in a row in the research period. While the level of effectiveness of groundwater tax collection is effective in 2015 to 2018 because it fulfil the Locally-Generated Revenue’s Target and also the change of it’s targets are still effective in 2019 because they meet the Locally-Generated Revenue’s Target even though they only meet 97% of the Change of Locally-Generated Revenue’s Target, but are considered (less effective) in 2020 due to the global pandemic that affects all sectors of the economic sector.